Biofilm Forming Bacteria Isolated From Human Eye Conjunctivitis and Keratitis Cases and their Ability to Adhere on Contact Lenses in vitro - Mohammed A. Mahdi; Munaff J. Abd Al-Abbas; Ahmed M. Alsamak (Institute of Medico-legal Publications Pvt Ltd, 2021)
One hundred bacteria isolated from conjunctivitis and keratitis showed 14 different bacterial species as Staphylococcus aureus, Staphylococcus epidermidis and Pseudomonas aeruginosa were the most. All 100 isolates were tested for their ability to form biofilm, 65 isolates (65%) showed positive for congo red agar (CRA) test with the exception of Enterobacter hormaechei, Staphylococcus haemolyticus and Bacillus pumilus species, while 84 isolates (84%) showed positive for microtiter plate assay except Bacillus pumilusspecies. Nevertheless, icaAD genes were detected in 75 isolates (75%) within all species. Although 100 bacterial isolates showed different results toward biofilm production tests, CRA, MTP assay and icaAD genes, but there was no significant difference found among these tests. Appliedally, the ability to adhere on contact lenses (In vitro) appeared Staphylococcus aureus has the highest adhesion 12(92.3%) followed by P. aeruginosa 3(75%) and Staphylococcus epidermidis 3(60%).